STRATEGI MANAJEMEN LIKUIDITAS DALAM MENJAGA STABILITAS BANK SYARIAH INDONESIA DI MASA KRISIS: UIN Sayyid Ali Rahmatullah Tulungagung - Lorenza Putri, Amanda Ika; Anjarwati, Ribut Peni; Wulandari, Ulfa Dwy Ayu; Asiyah, Binti Nur (PT. Media Edutama Nusantara, 2024)
Islamic banks face major challenges in maintaining their financial stability amidst global economic uncertainty. This article discusses the liquidity management strategies implemented by Bank Syariah Indonesia to maintain stability during the crisis using a qualitative literature study approach. Online observation data collection techniques include book sources, scientific journals, and reports issued by official institutions. Data analysis uses descriptive quantitative. From the research conducted, there are three liquidity management strategies in maintaining stability, namely liquid asset adequacy, merger policy, and NPF analysis. These strategies have a significant impact on the stability of Bank Syariah Indonesia during the crisis as evidenced by capital instruments, assets, and profits that continue to increase every year.